2019
DOI: 10.3390/en12142795
|View full text |Cite
|
Sign up to set email alerts
|

Design, Manufacturing and Characterization of Linear Fresnel Reflector’s Facets

Abstract: This paper presents a procedure for making facetted mirrors to use in linear Fresnel reflectors, considering the design of the transversal geometry, materials, and structure configuration. Four different assemblies of the structure that supports and shapes the mirror are documented and evaluated. An assembly that implies a curved, pleated aluminum rectangular plate with a thin silvered-glass mirror vacuum glued to the plate is defined as the optimal. The geometrical quality of the chosen mirror facet’s configu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Table 2 shows the summary of these values for all measurement positions. As can be seen from both Table 2 and Figure 7, despite the manual fabrication of the LFC prototype facets [12], a good homogeneity in the average concentration has been achieved for each of the 10 measurement positions.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Table 2 shows the summary of these values for all measurement positions. As can be seen from both Table 2 and Figure 7, despite the manual fabrication of the LFC prototype facets [12], a good homogeneity in the average concentration has been achieved for each of the 10 measurement positions.…”
Section: Resultsmentioning
confidence: 81%
“…Each row of primary reflector of the LFC is segmented into 10 facets; the facet size is 1 m long by 0.28 m wide. They were fabricated at PSA from 1 mm thick silvered glass mirrors and 3 mm thick curved aluminum sheet [12]. The curvature of the facets is cylindrical because although this geometry presents optical aberrations that do not appear in the case of parabolic geometry, it is constructively simpler and cheaper to manufacture.…”
Section: Geometry Of the Collector Systemmentioning
confidence: 99%
“…The maximum energy efficiency of 𝜂 = 81% for a plant latitude of 37.1° occurred for a field tilt of λ = 33.44°, while for a plant latitude of 24.1° the maximum energy efficiency of 𝜂 = 84% occurred for a field tilt of λ = 22.2°. While theoretically the optimum tilt should be very similar to the latitude of the plant, Pulido-Iparraguirre et al (2019) also found that the optimum tilt angle was lower (λ = 25.8° for a plant latitude of 37.1° North), due to seasonal variations in the sun angle. When provision was made for this variation, using an adjustable tilt angle, Zhu et al (2017) reported a 9% increase in the thermal efficiency to 𝜂 = 64%.…”
Section: Translating Mirrors and Receiversmentioning
confidence: 91%
“…Flat mirrors are designed in such a way that they have a larger reflective surface area in the very same amount of space compared to parabolic reflector that allows more solar energy to be captured. Additionally, they cost a lot less than cylindrical parabolic trough concentrators [27] [28]. Fig.…”
Section: Fresnel Mirror Concentratormentioning
confidence: 99%